FEELING THEIR WAY - Kirkby, Jagger Andersen (Culture and History: Student Research Papers, 2017)
In a bid to step away from a history of apartheid centred on African and Afrikaner nationalisms, the article redirects attention towards the white South African English-speaking community. An analysis of the emotional practices employed in the South African English-language press on Rhodesian unilateral independence in 1965 define the emotion work these practices carry out. The article concludes that this emotion work creates certain emotional narratives, which nuance a conventional view of the English-speaker as “unknown” and his attitudes towards the racial dilemma in South Africa as aloof, thus revealing a hitherto unprecedented proactivity in the English-speaker.